Corporate social responsibility and forward default risk under firm and industry heterogeneity - Mushafiq, Muhammad; Prusak, Błażej; Markiewicz, Magdalena (Entrepreneurial Business and Economics Review, 2024)
Objective: This study aims to evaluate the impact of corporate social responsibility on forward default risk (FDR) under the setting of firm and industry heterogeneity. Research Design & Methods: This study evaluated the impact of corporate social responsibility (CSR) on FDR using the data of 497 companies from 2007-2021 in the S&P 500 index, taking into account firm and industry heterogeneity aspects. This study utilized instrumental variable regression using the generalized method of moments (IV-GMM) estimation technique which is robust for controlling the pertinent issue of endogeneity. Findings: This study found a negative relationship between CSR and FDR in the full sample. From the firm size aspect, this study found that CSR is more effective in mitigating FDR in large-cap firms than in mid-cap firms. Firm age heterogeneity exhibited a distinct behaviour, as young and middle-aged firms had a stronger impact on FDR management in comparison to old firms. Industry heterogeneity showed that industries with higher customer interaction have a higher impact on corporate social responsibility to control FDR. Industries with lower customer interaction have a lower impact on corporate social responsibility and FDR. Implications & Recommendations: We proposed some policy recommendations based on the findings in the context of firm and industry heterogeneity. Especially the management of mid-cap and young corporations should improve the CSR policy to enhance CSR performance which would lead to stabilized protection against FDR. Similarly, consumer-intensive industries should also focus on enhancing CSR initiatives to decrease FDR. Non-consumer-intensive industries should focus on enhancing CSR policy and at the same time pay particular attention to communicating CSR results to end consumers to reduce FDR. Contribution & Value Added: This study is the first to explore CSR’s impact on financial parameters under heterogeneity.